A method for determining the grade of osteoporosis based on risk factors in postmenopausal women - AKYÜZ, GÜLSEREN DERYA; GÜNDÜZ, OSMAN HAKAN (SPRINGER LONDON LTD, 2005)
The aim of this study was to determine whether the probability of osteoporosis and osteopenia was affected by the risk factors, physical examination findings, or radiological investigations such as spinal X-rays in postmenopausal women. We assessed risk factors such as use of hormone replacement therapy, physical activity level, calcium intake, smoking, caffeine consumption, long-term immobilization, previous history of fracture, family history of fracture, presence of certain systemic diseases (hyperthyroidism or hyperparathyroidism), or use of medications (corticosteroids or others), physical examinations, and presence of vertebral fractures on spinal X-rays. Patients' bone mineral density (BMD) was evaluated using dual energy X-ray absorptiometry (DXA) in the lumbar spine, and we compared the risk factors between osteopenic and osteoporotic women according to DXA. We evaluated 235 postmenopausal women who attended our osteoporosis outpatient clinic. Those patients were divided into two groups as either osteopenic (n=67, mean age: 63.1 years) or osteoporotic (n=168, mean age: 66.2 years) according to WHO criteria. The lumbar spinal (L1-L2) T-score values were -1.5 +/- 0.6 and -3.1 +/- 0.6 in osteopenic and osteoporotic groups, respectively. There were significant differences between the two groups in terms of mean age and lumbar BMD (p=0.009 and p < 0.001, respectively). We also observed that vertebral tenderness on palpation, back pain, and existing vertebral fracture (fx) were significantly different between the osteopenic and osteoporotic groups (p < 0.05). As a result of the statistical analysis, we found an equation to determine osteopenic and osteoporotic women by using those four factors (age, vertebral tenderness on palpation, back pain, and existing vertebral fx) in multivariate stepwise logistic regression. The equation is as follows: Y (DXA) = -2.9024 + 0.044 (age in year) + 0.819 (vertebral fx) + 0.877 (pain) + 1.136 (vertebral tenderness). We can estimate whether a postmenopausal woman is osteopenic or osteoporotic based on these risk factors by using the stepwise logistic regression equation.
Keywords: osteopenia; osteoporosis; screening and diagnosis; vertebral fracture; BONE-MINERAL DENSITY; THERAPY; HORMONE; MEN